Pengalaman Mahasiswa Program Studi Gizi Menulis Artikel Ilmiah melalui Project Based Learning: Nutrition Students' Experience Writing Scientific Articles Through Project-Based Learning - Nur Qoyyimah , Atika Lisamawati (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study aims to describe the implementation of Project-Based Learning (PjBL) and to explore students’ responses, opportunities, and challenges in writing scientific articles. A qualitative approach using a case study design was employed in this research. The study was conducted at Universitas Kusuma Husada in Surakarta in the Bahasa Indonesia course (MKWU) of the Nutrition Study Program. Ten students were selected through purposive sampling. Data were collected through interviews, observations, and documentation, and then analyzed using the Miles and Huberman interactive model. The results of the study indicate that students responded positively to PjBL because it provided an active and meaningful learning experience. Students demonstrated improved understanding of citations, article structure, and academic language. PjBL also developed critical thinking skills, collaboration, and self-confidence. However, students face challenges in time management, finding references, and academic language. This study concludes that PjBL effectively supports Nutrition students’ scientific writing skills, provided that intensive guidance is provided during the stages where they encounter difficulties.